Small town, big mayor: Abstentionism in municipal elections in Uruguay, 2010-2020 - Buquet, Daniel; Cardarello, Antonio; Schmidt, Nicolás (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2024)
This article identifies the factors that have influenced varying levels of citizen involvement in municipal elections in Uruguay since 2010. Several studies show that turnout in local elections is lower than in national elections, whereas that participation increases as the size of the municipality decreases. However, in Uruguay turnout is very high in all elections because voting is compulsory. For that reason, we use a novel way to measure citizen involvement in subnational elections by quantifying the “partial blank vote” or level abstention, which captures the percentage of those who turn out to vote but abstain at one of the levels (departmental or municipal). We show that the inverse relationship between municipality size and electoral participation also holds, even when compulsory voting does not show it in turnout. In many small municipalities the votes for local authorities exceed those obtained by departmental authorities, thus inverting the relationship of the second level election model. Our findings allow us to observe varying levels of citizen involvement beyond the mere turnout to vote, which has been the only variable analyzed thus far by the academic community.